2015
DOI: 10.5194/amt-8-3047-2015
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and instrumental line shape characterization of a set of portable FTIR spectrometers for detecting greenhouse gas emissions

Abstract: Abstract.A comprehensive calibration procedure for mobile, low-resolution, solar-absorption FTIR spectrometers, used for greenhouse gases observations, is developed. These instruments commend themselves for campaign use and deployment at remote sites. The instrumental line shape (ILS) of each spectrometer has been thoroughly characterized by analyzing the shape of H 2 O signatures in open path spectra. A setup for the external source is suggested and the invariance of derived ILS parameters with regard to chos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
146
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(156 citation statements)
references
References 25 publications
(33 reference statements)
9
146
1
Order By: Relevance
“…Here, we find agreement between two DCS instruments that is an order of magnitude better and is comparable to that achieved with highly calibrated, state-of-the-art solar-looking FTS systems that retrieve vertical column measurements (Messerschmidt et al, 2011;Frey et al, 2015;Hedelius et al, 2016); how-ever, open-path DCS does not require instrument-specific calibrations (e.g., of the instrument line shape) and provides a very different capability by retrieving the dry mole fractions across regional, kilometer-scale paths over day and night on a mobile platform. Moreover, as the agreement between openpath DCS instruments is below the level of natural background fluctuations, future measurements can facilitate accurate inverse modeling to identify sources and sinks of carbon emission over regions.…”
Section: Introductionmentioning
confidence: 52%
“…Here, we find agreement between two DCS instruments that is an order of magnitude better and is comparable to that achieved with highly calibrated, state-of-the-art solar-looking FTS systems that retrieve vertical column measurements (Messerschmidt et al, 2011;Frey et al, 2015;Hedelius et al, 2016); how-ever, open-path DCS does not require instrument-specific calibrations (e.g., of the instrument line shape) and provides a very different capability by retrieving the dry mole fractions across regional, kilometer-scale paths over day and night on a mobile platform. Moreover, as the agreement between openpath DCS instruments is below the level of natural background fluctuations, future measurements can facilitate accurate inverse modeling to identify sources and sinks of carbon emission over regions.…”
Section: Introductionmentioning
confidence: 52%
“…PROFFIT is in wide use in the NDACC (e.g. Sepúlveda et al, 2014;Virolainen et al, 2014;Mengistu Tsidu et al, 2015), is in very good agreement with the official TCCON analysis (Dohe, 2013), and is also successfully applied for the analysis of spectra recorded with the EM27/SUN (Gisi et al, 2012;Frey et al, 2015). For the analysis of the low-resolution spectra, the methane, water vapour, HDO, and CO a priori profiles were adopted from the TC-CON processor.…”
Section: Results Of Atmospheric Retrievalsmentioning
confidence: 99%
“…model studies of greenhouse gases sources (Messerschmidt et al, 2013) and observation of local sources (Lindenmaier et al, 2014). Recently, several investigators demonstrated that portable low-resolution FTIR spectrometers still allow surprisingly precise and accurate measurements of column-averaged greenhouse gas abundances (Petri et al, 2012;Gisi et al, 2012;Frey et al, 2015). Such devices are a promising supplement to the TCCON, for performing measurements at remote sites, for mobile applications (Klappenbach et al, 2015), and for observations of dedicated sources and sinks on regional and smaller scales .…”
Section: Introductionmentioning
confidence: 99%
“…For the analysis of spectra recorded in the MIR, we use the retrieval algorithm PROFFIT (Hase et al, 2004), which is widely used within NDACC and for analyses of lowresolution spectra as recorded with EM27/SUN spectrometers (Bruker Optics GmbH, Germany; Gisi et al, 2012;Hase et al, 2015;Frey et al, 2015; Klappenbach et al, Figure 1. A priori VMR profiles used for the TCCON retrieval of NIR spectra (daily varying profile) and for the NDACC retrieval of MIR spectra (one fixed profile).…”
Section: Ndacc Retrieval Strategy For Comentioning
confidence: 99%